Perbedaan Harga Lahan Sebagai Akibat Terjadinya Fenomena Percampuran Ruang Bermukim di Wilayah Pinggiran Kota Semarang (Studi Kasus Perumahan Formal dan Informal di Kelurahan Pedalangan & Bulusan) - Wily Alfi Gustiana (Department of Urban and Regional Planning, Diponegoro University, 2013)
Suburbanization is a process to shape built areas as an impact urban development expansion (Wiratmaja, 2002:33). The real form of suburbanization is shift settlements activity towards suburban area. Therefore, many new development settlements are made to accommodate city core inhabitants at this time. Pedalangan Subdistrict and Bulusan which are part of Banyumanik District also Tembalang has been filled by new formal settlements such as Graha Estetika, Graha Sapta Asri, Grand Tembalang Regency, Villa Tembalang, and Korpri. Whereas, urban settlements in Pedalangan Subdistrict also Bulusan is not only consist of estate that is part of formal settlements but also Kampong which is a part of informal settlements. Mostly, new developments of formal settlements build nearby informal settlements that have been there first. These things have a potential thing to emerge disparity related social, economic, cultural, physical, and spatial aspect. One of the most spatial impacts that will appear is the land price differentiation between formal and informal settlements. Based on that phenomenon is formulated statement research “There was land price differentiation as an impact of mix urban settlements between formal and informal settlements in suburban area.” This research aims to identify land price differentiation that occurred as an impact of mix urban settlements in suburban area. In order to achieve that purpose, the process of identification and analysis need to carry on towards factors that could affect the land price such as land physic characteristic, accessibility, facility and infrastructure availability, ownership status, and environmental quality. This research will use quantitative descriptive analysis with descriptive statistics based on the results of questionnaires and observation. Based on findings, that indicate there are only two factors that can be land price differentiation between formal and informal settlements is the ease of accessibility and facility and infrastructure availability. The land physic characteristic, ownership status, and environmental quality can not to identify land price differentiation because of these characteristics of each these factors are almost equally between formal and informal settlements. Based on the results of the study findings it can be concluded that there are land price differentiation between formal and informal settlements caused by mix urban settlements. It also need a form of problem solve such as zoning regulation, land conversion regulation, land transaction regulation, land taxation, and regulation of new building that aims to control development of suburban areas to be more focused by considering the integration process physical, social, and economic community.